(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. The kidney is the main source of serum Klotho production. Immunosuppressive agents could affect the kidney in this regard. The effect of the ACE gene polymorphism on Klotho production is a less studied area. This study aimed to assess serum Klotho and ACE gene in a group of stable kidney transplant recipients. Materials and Methods. In a cross-sectional study, 30 kidney transplant recipients with stable allograft function and 27 healthy young individuals were assessed for their serum Klotho levels. The ACE gene polymorphisms were studied in both groups. Results. Klotho level was higher in kidney transplant recipients than the controls, but the difference was not significant (2.76 ± 2.41 ng/mL versus 2.01 ± 1.41 ng/mL, respectively). In both groups, serum Klotho level was higher in those with the I>I polymorphism, the men, those with higher glomerular filtration rate, and younger individuals, but the differences did not reach a significant level. Higher body mass index was significantly associated with lower serum Klotho level in both groups. Conclusions. Klotho level after kidney transplantation meets the range in healthy individuals, and it is not affected by the ACE gene polymorphism.